The Nurse in the University: A History of University Education for South African Nurses: A Case Study of the University of the Witwatersrand - Simonne Horwitz (Nursing Research and Practice, 2011)
This paper charts the history and debates surrounding the introduction of academic, university-based training of nurses in South Africa. This was a process that was drawn out over five decades, beginning in the late 1930s. For nurses, university training was an important part of a process of professionalization; however, for other members of the medical community, nursing was seen as being linked to women's service work. Using the case-study of the University of the Witwatersrand, one of South Africa's premier universities and the place in the country to offer a university-based nursing program, we argue that an historical understanding of the ways in which nursing education was integrated into the university system tells us a great deal about the professionalization of nursing. This paper also recognises, for the first time, the pioneers of this important process.